ANALISIS FAKTOR-FAKTOR PEMILIHAN LOKASI USAHA TERHADAP KESUKSESAN USAHA JASA MIKRO DI KECAMATAN SUNGAI KUNJANG - -, Nur Wahyudi (EKONOMIA, 2014)
This study aims to identify and analyze the factors Site Selection Business Services Business Success Against Micro in Kecamatan Sungai Kunjang. Specifically to analyze whether there is a significant influence of the factor proximity to infrastructure, business environment and the cost of the location of the business success.Formulation of the problem in this study is : "Is business location based on proximity to infrastructure factors significantly influence the success of a business ? s the site selection business based on the business environment factors significantly influence the success of a business?, Is the business location based on the location cost factors significantly influence the success of a business?, is the business site selection based on factors (proximity to infrastructure, business environment, the cost of location) significantly influence the success of the business? ".Basic theory in this study are: Operations Management focuses on business Siting. The hypothesis in this study is: "The proximity to infrastructure significantly influence the success of a business, the business environment significantly influence the success of a business, the cost of the location of a significant effect on the success of the business, and proximity to infrastructure, business environment and the cost of the location of a significant effect on the success of the business".Methods of data analysis in this study is the Multiple Linear Regression Analysis. The results showed that the proximity to infrastructure, business environment, and the cost of the location of a significant effect on business success (Y = 0.145 + 0,327X2 0,272X1 + 0,398X3).Based on the results of the t test, proximity to infrastructure variables significantly influence the success of a business, the business environment variables significantly influence the success of the business, and the variable cost of the location of a significant effect on business successOf the three independent variables, the cost of location is a variable that has the greatest influence over the other two variables.